The Influence of Promotion on Customer Loyalty Through Brand Ambassadors of Nabati Products on Generation Z in DKI Jakarta - Salsabilah Humairoh; Nor Lailla (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The objectives of this study are (1) To determine the effect of promotion on customer loyalty. (2) To determine the effect of promotion on brand ambassador. (3) To determine the effect of brand ambassador on customer loyalty. (4) To determine the effect of promotion on customer loyalty through brand ambassador. The population in this study were Nabati consumers in DKI Jakarta. The sample used was the accidental sampling formula with a total sample of 300 samples. The data was processed using the Partial Least Square (PLS) method. From the analysis results, it was found that 65.9% of customer loyalty was influenced by promotions and brand ambassadors.